DEVELOPMENT AND VALIDATION OF UPLC-PDA METHOD FOR QUALITY ASSESSMENT OF BIOMARKERS IN POLYHERBAL ANTI-DIABETIC FORMULATION - Lilhare, Mangeshkumar S.; Chouhan, Disha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Background/Objectives: It consist of Gymnema sylvestre, Momordica charantia, Trigonella foenum-graecum, Azadirachta indica, Syzygium cumini, has been widely used to treat Diabetes. In the present study, a Ultra-performance liquid chromatography with photodiode array detector (UPLC–PDA) method for the simultaneous quality assessement of the five biomarkers components, i.e., Gymnemic acids from Gymnema sylvestre, Charantin and momordicin from Momordica charantia,4-hydroxyisoleucine and trigonelline from Trigonella foenum-graecum, Quercetin and rutin from various herbs, Gallic acid and ellagic acid as phenolic markers was developed. The main objectives of this research work to develop and optimize a sensitive and selective UPLC-PDA method for simultaneous determination of key biomarkers in polyherbal anti-diabetic formulations with enhanced resolution and reduced analysis time compared to conventional HPLC methods & to validate the developed UPLC-PDA method according to ICH Q2(R1) guidelines, evaluating all critical validation parameters including specificity, linearity, accuracy, precision, detection limits, quantitation limits, robustness, and system suitability to ensure method reliability and regulatory compliance. Methods: The developed UPLC–PDA assay for quality assessement of biomarkers for herbal anti diabetic formulation was validated with respect to linearity, limit of detection (LOD), limit of quantification (LOQ), recovery, and precision. Results: In the regression equation of the calibration curve, the coefficient of determination was (r²) ≥ 0.999 and LOD and LOQ were 0.010–0.022 μg/mL and 0.033–0.070 μg/mL, respectively. Recovery and precision (relative standard deviation) were 98–100% and <2.0%, respectively. In this analytical method, Five compounds were detected and Succesfully validated by UPLC-PDA method. Conclusions: The development and validation of an analytical method could be used to obtain basic data for the quality assessment of biomarkers in polyherbal anti-diabetic preparation by the use of UPLC-PDA.